Hot compressed water pretreatment and surfactant effect on enzymatic hydrolysis using agave bagasse - Pino, Marcela Sofia (2021)
Agave bagasse is a residual biomass in the production of the alcoholic beverage tequila, and therefore, it is a promising raw material in the development of biorefineries using hot compressed water pretreatment (hydrothermal processing). Surfactants application has been frequently reported as an alternative to enhance monomeric sugars production efficiency and as a possibility to reduce the enzyme loading required. Nevertheless, the surfactants action mechanisms in the enzymatic hydrolysis is still not elucidated. In this work, hot compressed water pretreatment was applied on agave bagasse for biomass fractionation at 194 °C in isothermal regime for 30 min, and the effect of non-ionic surfactants (Tween 20, Tween 80, Span 80, and Polyethylene glycol (PEG 400)) was studied as a potential enhancer of enzymatic saccharification of hydrothermally pretreated solids of agave bagasse (AGB). It was found that non-ionic surfactants show an improvement in the conversion yield of cellulose to glucose (100%) and production of glucose (79.76 g/L) at 15 FPU/g glucan, the highest enhancement obtained being 7% regarding the control (no surfactant addition), using PEG 400 as an additive. The use of surfactants allows improving the production of fermentable sugars for the development of second-generation biorefineries.